The Labor Supply of Fixed-Wage Workers: Estimates from a Real Effort Experiment - Jeffrey P. Carpenter (Institute for the Study of Labor (IZA), 2016)
Fixed-wage workers comprise the bulk of the labor force and yet little is known about how they respond to wage changes. Given recent interest in theories of reciprocity and intrinsic motivation and their implications for effort provision, the neoclassical prediction seems less obvious today. To better understand the motivation of these workers, I estimate their labor supply using a real effort experiment. Two results stand out. First, no one theory seems to fit the pooled data. On average, people work considerably harder than the minimum but they do not respond to changes in the wage. Second, pooling the data is deceptive because there seem to be distinct types with differing responses to the wage. Most workers can be classified as reciprocal or intrinsically motivated and, indeed, these types respond as theory would predict: reciprocators return wage gifts with increased effort and extrinsic incentives crowd out motivation for intrinsic workers.
Keywords: C91; J22; 330; labor supply; fixed wage; reciprocity; intrinsic motivation; real effort; experiment